New species of flightless katydids from South Africa (Orthoptera: Tettigoniidae: Meconematinae) - Naskrecki, Piotr; Bazelet, Corinna S.; Spearman, Lauren A. (Zootaxa, 2008)
Four new species (Amyttacta marakelensis n. sp., A. farrelli n. sp., Paracilacris mordax n. sp., and P. periclitatus n. sp.) of South African Meconematinae (Orthoptera: Tettigoniidae) are described, and keys to genera Amyttacta and Paracilacris are provided.